PELAKSANAAN PENEGAKAN HUKUM BAGI ANGGOTA KEPOLISIAN YANG MELANGGAR KODE ETIK DALAM PENYALAHGUNAAN NARKOTIKA - umar dinata (Prodi Ilmu Hukum Fakultas Hukum Universitas Muhammadiyah Riau, 2021)
In Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia, the functions and duties of the Police are expanded to include maintaining security and public order, law enforcement, protection and protection and services to the community by upholding human rights, but there are some police officers who even abuse their authority by participate in the use and distribution of illegal drugs or drugs. This of course can lead to a loss of public trust in the police to guarantee legal certainty or provide legal protection to the community. The problem is how is law enforcement for members of the police who violate the code of ethics, what are the obstacles and efforts faced in law enforcement against members of the police who violate the code of ethics, the code of professional ethics of the police as stipulated in the regulation of the chief of police no. 7 of 2006 and Regulation of the National Police Chief No. 8 of 2006, is a moral code with the hope of growing a high commitment for all members of the National Police to obey and implement the Police Professional Code of Ethics